2021
DOI: 10.1101/2021.02.15.21251723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Review and Scientific Rating of Commercial Apps Available in India for Diabetes Prevention

Abstract: BACKGROUND Scientific evidence for digital health applications (apps) which claim to help in the prevention and management of Type 2 diabetes (T2D) is limited. OBJECTIVES We aimed to evaluate the quality of currently available health apps for prevention of T2D amongst Asian Indians. METHODS Using the keywords, diabetes prevention, healthy lifestyle and fitness, a total of 1486 apps available in India via Google Play were assessed for eligibility by two independent reviewers. After initial screening using spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…71 A systematic study has reported HealthifyMe as being good quality and user-friendly for the prevention of T2D among Asian Indians. 55 A healthcare start-up, Orbuculum, uses AI on genomic data to forecast the risk of developing diabetes. 69 Wealthy, another venture, offers affordable AI-based digital diabetes coaching solution to motivate Indian patients with T2D for diabetes self-management and to improve their QoL.…”
Section: Smartphone-based Retinal Photographymentioning
confidence: 99%
See 1 more Smart Citation
“…71 A systematic study has reported HealthifyMe as being good quality and user-friendly for the prevention of T2D among Asian Indians. 55 A healthcare start-up, Orbuculum, uses AI on genomic data to forecast the risk of developing diabetes. 69 Wealthy, another venture, offers affordable AI-based digital diabetes coaching solution to motivate Indian patients with T2D for diabetes self-management and to improve their QoL.…”
Section: Smartphone-based Retinal Photographymentioning
confidence: 99%
“…The results suggested two apps ‘Google Fit: Health and Activity Tracking’ and ‘HealthifyMe—Diet plan, Health and Weight Loss’ as being user-friendly and reliable quality. 55 Nevertheless, substantial evidence on the efficiency of these apps is still lacking.…”
Section: Real-world Evidence On the Success Metrics Of Digital Technologiesmentioning
confidence: 99%